2016
DOI: 10.7763/ijcte.2016.v8.1068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Model of the Visual Fatigue on the 3D Stereoscopic Video

Abstract: Abstract-We propose content dependent factors to be an argument of evaluation model of visual fatigue. The content factors we choose are the strength and size of the excessive disparity range, the complexity of the background objects, the variation of the motion-depth, the contrast of the objects in the scene. We verify that these factors have a relationship with visual fatigue through the experiment and suggest methods to extract the degree of these factors automatically.Index Terms-Content based fatigue fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, Sohn et al proposed object-dependent disparity features to predict the visual discomfort in stereoscopic 3D images [17]. So et al combined the strength and size of the excessive disparity range, the complexity of the background objects, the variation of the motion-depth, and the contrast of the objects in the scene to evaluate visual fatigue [18]. Ying et al proposed a visual comfort assessment based on scene mode classification and showed that the proposed method performs higher assessment accuracy than some state-of-the-art methods [19].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Sohn et al proposed object-dependent disparity features to predict the visual discomfort in stereoscopic 3D images [17]. So et al combined the strength and size of the excessive disparity range, the complexity of the background objects, the variation of the motion-depth, and the contrast of the objects in the scene to evaluate visual fatigue [18]. Ying et al proposed a visual comfort assessment based on scene mode classification and showed that the proposed method performs higher assessment accuracy than some state-of-the-art methods [19].…”
Section: Resultsmentioning
confidence: 99%
“…Visual fatigue, also known as eye fatigue, refers to the excessive strain experienced by the visual system due to prolonged or intensive visual tasks [1] [2]. It is a common issue faced by individuals who engage in activities such as prolonged computer usage, reading for extended periods, or driving long distances.…”
Section: Introductionmentioning
confidence: 99%
“…Most fatigue monitoring algorithms based on electrical signals use blink frequency and average eye closing time as indicators to determine the state. Some studies also perform time-frequency conversion on the acquired EOG signals, extract features from the frequency domain, and perform fatigue analysis [27] [28]. However, because this method is nonlinear in nature, it has its own limitations [29].…”
Section: Introductionmentioning
confidence: 99%
“…Liuye Yao [10] used BP neural network to predict the fatigue caused by stereo vision. BP neural network has the function of nonlinear mapping, and on this basis, it can learn, organize, and adapt itself [11]. Therefore, this paper used a three-layer BP neural network to establish a predictive model of operators' mental load.…”
Section: Introductionmentioning
confidence: 99%